Unveiling a family of spiro-β-lactams with anti-HIV and antiplasmodial activity via phosphine-catalyzed [3+2] annulation of 6-alkylidene-penicillanates and allenoates - Alves, Américo J. S.; Alves, Nuno G.; Bártolo, Inês; Fontinha, Diana; Caetano, Soraia; Prudêncio, Miguel; Taveira, Nuno; Pinho e Melo, Teresa M. V. D. (Frontiers in Chemistry, 2022)
The molecular architecture of spirocyclic compounds has been widely explored within the medicinal chemistry field to obtain new compounds with singular three-dimensional pharmacophoric features and improved bioactivity. Herein, the synthesis of 68 new spirocyclopentene-β-lactams is described, resulting from a rational drug design and structural modulation of a highly promising lead compound BSS-730A, previously identified as having dual antimicrobial activity associated with a novel mechanism of action. Among this diverse library of new compounds, 22 were identified as active against HIV-1, with eight displaying an IC50 lower than 50 nM. These eight compounds also showed nanomolar activity against HIV-2, and six of them displayed micromolar antiplasmodial activity against both the hepatic and the blood stages of infection by malaria parasites, in agreement with the lead molecule’s bioactivity profile. The spirocyclopentene-β-lactams screened also showed low cytotoxicity against TZM-bl and Huh7 human cell lines. Overall, a family of new spirocyclopentene penicillanates with potent activity against HIV and/or Plasmodium was identified. The present structure–activity relationship open avenues for further development of spirocyclopentene-β-lactams as multivalent, highly active broad spectrum antimicrobial agents.